Analisis Kesalahan Simple Past Tense pada Materi Kuliah Bahasa Inggris Dasar (Studi Kasus pada Kelas 64.1c.25 Jurusan Manajemen Fakultas Ekonomi & Bisnis 2022/2023 UBSI) - Mursyid Kasmir Naserly (Journal on Education, 2023)
This study analyzes the errors in the usage of the simple past tense formula by 20 students enrolled in the Basic English course in the Department of Management, Faculty of Economics and Business, Bina Sarana Informatika University. The research data were collected from the students' exercise answers to evaluate their understanding of the formula. The research method employed was qualitative descriptive. The results of the study indicate a common error frequently encountered, which is the misuse of sentence elements that do not correspond to the simple past tense formula. This error is attributed to the students' negligence, lack of precision in completing assignments, and the mixing of formulations with other tenses. Data were collected through direct observation of the students. The aim of this research is to gain a better understanding of the common errors in using the simple past tense formula, particularly in the context of teaching basic English at the university level.